2009
DOI: 10.3390/ma2041796
|View full text |Cite
|
Sign up to set email alerts
|

Combined Thermodynamic-Kinetic Analysis of the Interfacial Reactions between Ni Metallization and Various Lead-Free Solders

Abstract: In this paper we will demonstrate how a thermodynamic-kinetic method can be utilized to rationalize a wide range of interfacial phenomena between Sn-based lead-free solders and Ni metallizations. First, the effect of P on the interfacial reactions, and thus on the reliability, between Sn-based solders and electroless Ni/immersion Au (ENIG) metallizations, will be discussed. Next, the effect of small amounts of Cu in Sn-based solders on the intermetallic compound (IMC), which forms first on top of Ni metallizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 65 publications
1
9
1
Order By: Relevance
“…In the backscattered electron image of Figure in the interfacial zone during ageing. This was not observed in the current investigation after three months at 150°C or 200°C, most likely because the Au capping layer on the ENIG used was much thinner than in [23]. The transformation of NiSn4 or (Au,Ni)Sn4 eutectic did not go to completion at 150C in the 3 month time frame of the present study, indicating that decomposition would depend on the working environment of a solder joint and it is highly likely to be ongoing throughout its life.…”
Section: Ag/enig Joints At 150°ccontrasting
confidence: 60%
“…In the backscattered electron image of Figure in the interfacial zone during ageing. This was not observed in the current investigation after three months at 150°C or 200°C, most likely because the Au capping layer on the ENIG used was much thinner than in [23]. The transformation of NiSn4 or (Au,Ni)Sn4 eutectic did not go to completion at 150C in the 3 month time frame of the present study, indicating that decomposition would depend on the working environment of a solder joint and it is highly likely to be ongoing throughout its life.…”
Section: Ag/enig Joints At 150°ccontrasting
confidence: 60%
“…Ni acts as a diffusion barrier layer for Cu/ Sn-based solders in electronics, since the reaction rate of Ni with Sn is typically several orders of magnitude lower than that of Cu with Sn. 12,13 Use of Ni has been associated with improvement in solidification microstructures, increased volume fraction of eutectic phase, and lower propensity for interfacial IMCs to crack during service. 14 Though ENIG is suggested for long-term applications, it is prone to black pad, which forms during the plating process and can lead to early failure.…”
Section: Introductionmentioning
confidence: 99%
“…Laurila and Vuorinen [15] also found that Ni 3 P IMC formation can be suppressed when the P content reached 30 at%. However, the researchers did not mention the exact reason of what was happening to the surface of the coated copper when different P content was used.…”
Section: Introductionmentioning
confidence: 89%